Poverty, social injustice, and health - Barry S. Levy (Social Medicine Publication Group, 2013)
Approximately 46 million Americans live below the poverty line, and about 2.5 billion people globally live on less than $2 a day. Poor people have higher rates of morbidity, mortality, and disability, and less access to medical care and preventive services. They have more exposure to environmental health hazards. They are less likely to have access to healthful food. And they are more likely to be victims of violence. Much needs to be done to address the social injustices of poverty, including documentation and research, awareness-raising, and improved access to medical care, preventive services, education, job training, employment opportunities, and adequate housing. Health professionals must be culturally competent to address the medical needs of poor people, and socially and politically competent to address the social contexts that keep poor people poor. Victor W. Sidel, MD, has done important work to address poverty, and he has created a huge legacy for health, peace, and social justice.